Rancang Bangun Sistem Informasi Pengajuan Cuti Pegawai Berbasis Web pada PT. Mitratiga Perkasa Abadi - Muhammad Ajie Rizaldi; Aji Primajaya (Jurnal Ilmiah Wahana Pendidikan, 2022)
With the rapid development of information technology in this era of globalization, it is possible for every company organization to increase company productivity by utilizing the complexity of information technology. Information technology has many uses, one of which is in the field of Human Resource Management (HR) which is commonly referred to as Human Resource Information Systems. The problem that occurred at PT. Mitratiga Perkasa Abadi is currently the leave request mechanism is still using the manual method. Employees often don't know how much time is left for vacation, and vacation requests still use forms or cards that must be filled out and submitted to the department that handles them. Employee performance is also expected to improve by implementing good leave management. It is expected that the company or organization can develop as well as possible through good employee performance. This study aims to build an Information System for Employee E-Leave for PT. Mitratiga Perkasa Abadi is web-based with the aim of saving time and being transparent, so that employee performance becomes better and efficient. Website development is written using Node JS, while the website framework uses Expresss JS with the MVC concept and MongoDB database.